2017
DOI: 10.1016/j.amjmed.2017.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Diagonal Earlobe Crease (Frank's Sign): A Predictor of Cerebral Vascular Events

Abstract: Frank's sign could predict ischemic cerebrovascular events. Patients with classical cardiovascular risk factors had Frank's sign at a higher frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
(29 reference statements)
3
18
0
5
Order By: Relevance
“…White-matter lesions accompanied by cognitive decline are also considered to be linked to activation of platelet function [100]. In contrast to these factors, diagonal ear lobe crease (DELC) has been proposed as a marker for atherosclerotic disease [101,102]. Interestingly, DELC was more frequently found in persons with VCI than in cognitionnormal persons.…”
Section: Other Vascular Risk Factors For Wmhs-related Cognitive Deficitmentioning
confidence: 99%
“…White-matter lesions accompanied by cognitive decline are also considered to be linked to activation of platelet function [100]. In contrast to these factors, diagonal ear lobe crease (DELC) has been proposed as a marker for atherosclerotic disease [101,102]. Interestingly, DELC was more frequently found in persons with VCI than in cognitionnormal persons.…”
Section: Other Vascular Risk Factors For Wmhs-related Cognitive Deficitmentioning
confidence: 99%
“…This possibility would explain why the independent association between ELC and cardiovascular events was not significant in the present study. Although the mechanisms leading to the development of ELC are still unclear, previous studies in non-dialysis populations have shown ELC to be associated with well-known traditional cardiovascular risk factors, such as hypertension (9,(12)(13)(14), smoking (9,13,22), obesity (22), and diabetes (12,14,23). Hemodialysis patients have a higher prevalence of these traditional factors, as well as several non-traditional risk factors, such as anemia, hyperhomocysteinemia, chronic kidney disease-mineral bone disorder (CKD-MBD), oxidative stress, malnutrition, and chronic inflammation, than non-dialysis patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…The earlobe crease (ELC), also called Frank's sign (7), is a wrinkle extending from the tragus to the outer border of the earlobe. Several studies in non-dialysis populations have described ELC as a predictor of future CVD, including coronary heart disease (8)(9)(10)(11), cerebrovascular disease (12), and peripheral vascular diseases (13,14). The presence of ELC, which can be assessed easily without any test, might function as a visible prompt for both physicians and patients to screen for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have described an association between Frank’s sign and the presence of diabetes, hypertension [ 11 , 13 ], myocardial infarction and coronary artery disease [ 6 , 7 ] in patients of both sexes. According to these studies, this easily identifiable sign could be valuable in the screening of patients at high risk of having silent coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%